Effect of compound polysaccharide on immunity, antioxidant capacity, gut microbiota, and serum metabolome in kittens - Xie, Yixuan; Jian, Shiyan; Zhang, Limeng; Deng, Baichuan (Frontiers in Microbiology, 2025)
IntroductionThis study was conducted to investigate the effects of compound polysaccharides (CP), composed of Astragalus polysaccharide and Poria cocos polysaccharide, on immunity, antioxidant capacity, gut microbiota, and serum metabolome in kittens.MethodsA total of 14 4-month-old kittens, with an average body weight of 2.39 kg, were used in a 56-day experiment. They were randomly assigned to the control (CON) group (n = 7) and CP group (n = 7). Blood samples and fresh feces were collected at the end of the experimental period.ResultsThe results displayed that supplementation with CP increased the concentrations of serum immunoglobulin A, immunoglobulin G, interleukin 6, and tumor necrosis factor-α (p < 0.05). However, there was no difference in the concentrations of serum amyloid A between the two groups (p > 0.05). Furthermore, the serum biochemical parameters of all the kittens were within the reference range. The relative abundance of beneficial bacteria (norank_f__Butyricicoccaceae and Bacteroides plebeius) was higher in the CP group (p < 0.05), while the opportunistic pathogen (Anaerotruncus) was lower in the CP group (p < 0.05). In addition, serum metabolomic analysis demonstrated that the differential metabolites, including arachidonic acid, dihomo-gamma-linolenic acid, and glycine, and the relevant metabolic pathway, including glyoxylate and dicarboxylate metabolism, glycine, serine, and threonine metabolism, and biosynthesis of unsaturated fatty acids, were implicated in regulating immune function in the kitten after CP treatment.ConclusionCP supplementation can enhance immune function in kittens and increase the relative abundance of beneficial gut microbiota, and does not lead to generalized inflammation. Dietary supplementation with CP may generate nutritional benefits in kittens, and this study offers insight into the development of functional pet food for kittens.